NGINX cookbook : advanced recipes for operations - DeJonghe, Derek (O'Reilly Media, 2017)
NGINX is one of the most widely used web servers available today, in part because of its capabilities as a load balancer and reverse proxy server for HTTP and other network protocols. The 2019 edition of this popular cookbook provides more than 80 practical recipes to help you set up and use this open source server to solve problems in various use cases. For professionals who understand modern web architectures, such as n-tier or microservice designs, and common web protocols, including TCP and HTTP, these recipes provide proven solutions for security, software load balancing, and monitoring and maintaining NGINX's application delivery platform. You'll also explore advanced features of both NGINX and NGINX Plus, the free and licensed versions of this server. You'll find recipes for: High-performance load balancing with HTTP, TCP, and UDP Traffic management and A/B testing Managing programmability and automation with dynamic templating and the NGINX Plus API Securing access through encrypted traffic, secure links, HTTP authentication subrequests, and more Deploying NGINX to AWS, Azure, and Google cloud-computing services Using Docker to deploy containers and microservices Debugging and troubleshooting, performance tuning, and practical ops tips.